"Bank-Wreckers, Defaulters, and Embezzlers": America's Popular Fear and Fascination with the Misappropriation of Bank Deposits during the Gilded Age and Progressive Era. (21st January 2018) - MACKAY, THOMAS A.
Abstract : This article explores how "bank-wreckers, defaulters, and embezzlers" were popularly perceived during Gilded Age and Progressive Era America, and how they contributed to a broader concern over the safety of deposits and helped drive efforts to achieve greater financial security. Their actions, often described as "wrecking, " referred to instances in which a banking institution was damaged or destroyed due to the embezzlement or general misappropriation of depositor funds by bank officials or employees. Wrecking occurred inside and outside of the era's major banking panics, and attracted popular and critical attention over this period, especially between the 1880s and the early 1910s. It is argued that this phenomenon resonated within the popular imagination, which was reflected, reinforced, and even instilled through the media, and that this helped sustain doubts on the reliability of the nation's banks and bankers. This article shows how notions of class, character, and gender influenced how people thought about the problem: wrecking demonstrated that respectability could be illusory and that men of the era could be tempted to "get rich quick" through dubious means. Some of the major attempts to resolve the problem are also discussed to highlight how efforts to prevent wrecking relate to the period's general push to bolster economic stability. Ultimately, the article shows how seemingly disparate events can aggregate into a larger problem, which can in turn motivate solutions and reforms.